Trust in Surveillance: A Reply to Etzioni - Whelan, Glen (Journal of business ethics, 2019)
Etzioni has recently proposed that the success of Internet enabled commerce is surprising due to what I label the “trust in strangers” problem. In here responding to Etzioni, I argue that the “trust in strangers” problem effectively dissolves once it is recognized that current manifestations of Internet commerce are not associated with high levels of anonymity, but rather, with high levels of surveillance. In doing so, I first outline how data capitalism and security considerations have contributed to Internet surveillance being close to ubiquitous. Following this, I differentiate between three types of surveillance—i.e. top-down, bottom-up, networked—that many people who digitally connect rely upon. In concluding, I emphasize my basic argument. Namely, that it is “trust in surveillance”, rather than “trust in strangers”, that supports current manifestations of commerce online.